Peran Self-Efficacy Dalam Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa di Sekolah Dasar - Devi Purwanti; Kharisma Yusuf Khairunnisa; Laely Rizki Maulida (Advances In Education Journal, 2026)
The purpose of this study is to describe the role of self-efficacy in improving elementary school students' mathematical problem-solving abilities. Self-efficacy is the belief in one's learning process or ability to complete various tasks. The approach used was descriptive qualitative, using interviews and observations with six fourth-grade students and their homeroom teachers. The results showed that students with high self-efficacy demonstrated self-confidence while learning, were more diligent, did not give up easily, and were active in facing learning challenges. Factors influencing self-efficacy include successful experiences, teacher and parental support, and peer influence. These findings confirm that self-efficacy is an important pillar in strengthening elementary school students' mathematical problem-solving abilities. Teachers and parents have a crucial role to play in fostering self-efficacy in children, which can ultimately impact their enthusiasm and resolve problems in everyday life.